Reservoir effect and the role of low current density regions on electromigration lifetimes in copper interconnects - Shao, W. (2012)
Electromigration (EM) in copper dual-damascene interconnects with extensions(also described as overhang regions or reservoirs) in the upper metal (M2) were investigated. It was found that as the extension length increases from 0 to 60 nm, the median-time-to-failure increased from 50 to 140 h, representing a ∼200% improvement in lifetimes. However, further increment of the extension length from 60 to 120 nm did not result in any significant improvement in EM lifetimes. Based on calculations of current densities in the reservoir regions and recently reported nucleation, void movement, and agglomeration-based EM phenomena, it is proposed that there is a critical extension length beyond which increasing extension lengths will not lead to longer EM lifetimes.